Trunk muscle strength and lumbo-pelvic kinematics in adolescent athletes: Effects of age and sex - Arampatzis, A.; Frank, J.; Laube, G.; Mersmann, F. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Considering their potential relevance for low-back pain, we investigated trunk muscle strength, sagittal lumbopelvic alignment while standing and lumbopelvic rhythm during trunk flexion in adolescent athletes and with regard to the effects of age and sex. Twenty-two early adolescent (EA: 13-15 years, 10 females) and 28 late adolescent (LA: 16-19 years, 14 females) high level athletes (training duration more than 12 hours per week) participated in the study. We measured trunk extension and trunk flexion moments during maximum voluntary isometric contractions using a dynamometer. Further we examined lumbo-pelvic kinematics in the upright standing position and during forward trunk bending using two 3-dimensional accelerometers. Using a lineal regression model in which the flexion moment from each participant was used as predictor for the corresponding extension moment, we found higher residuals (p<0.001) in the EA compared to LA, indicating greater imbalances in the trunk muscle strength in EA. We found a higher lordosis in the upright position, greater pelvic rotation and greater lordotic posture during the forward bending in females (p<0.01). The found age-related imbalances and sex- related characteristics in lumbo-pelvic kinematics affect the neuromuscular control of trunk stability and the magnitude of spine loading. We recommend the implementation of specific coordination and stabilization programs for muscle groups that contribute to lumbo-pelvic kinematics and training routines that support a balanced strength development within the trunk muscles in adolescent athletes.